Elevated Temperature Fatigue Life Investigation of Aluminium Alloy based on the Predicted S-N Curve - Zakaria, Kamarul Ariffin (Unitversiti Teknologi Malaysia, 2013)
This paper discusses a methodology used to predict the stress-life (S-N) curve at elevated temperatures based on the normal S-N curve. Fatigue tests were performed under stress control at room temperature in accordance with the ASTM E466 standard to obtain a normal S-N curve. In addition, the tests were performed at both room and elevated temperatures using constant-amplitude, high-to-low sequence, and low-to-high sequence loadings to investigate the effect of the load sequence at elevated temperatures on fatigue life. Three elevated temperature regimes at 70 to 250C were chosen based on the maximum temperature of the engine mount bracket and the cylinder head that can be reached during normal service. The results show that the fatigue lives were significantly affected by the load sequences at both room and elevated temperatures. Furthermore, the existing fatigue data obtained at elevated temperatures can be used to predict the corresponding S-N curves.